Percutaneous Screw Fixation vs. Casting for Non-Displaced or Minimally Displaced Scaphoid Waist Fractures: A Meta-Analysis of Randomized Controlled Trials - Volfson, Emily; Essa, Ahmad; Paul, Ryan; Chan, Andrea; Zuo, Kevin J.; Khan, Shawn; Persitz, Jonathan (Journal of Wrist Surgery, 2025)
The optimal treatment for non-displaced scaphoid waist fractures remains uncertain. This meta-analysis examined whether percutaneous screw fixation offers improved clinical and functional outcomes compared with cast immobilization, while also evaluating safety and the need for secondary procedures.A systematic review of MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Cochrane databases was conducted through May 2025. Randomized controlled trials comparing percutaneous or mini-open screw fixation to cast immobilization in adults with non-displaced or minimally displaced scaphoid waist fractures were included. Six trials (n = 639; 315 surgical and 324 nonsurgical) met the inclusion criteria. Outcomes were pooled using random-effects models when substantial heterogeneity was present; otherwise, a fixed-effect model was applied. Risk of bias was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool, and certainty of evidence was graded with Grading of Recommendations Assessment, Development and Evaluation (GRADE).Percutaneous screw fixation was associated with a lower risk of nonunion (1.6% vs. 7.1%; risk ratio [RR] 0.22; 95% confidence interval [CI]: 0.09–0.57; p = 0.002; I2 = 33.4%), faster time to union (mean difference −3.8 weeks; 95% CI: −5.20 to −2.44; p < 0.001), and earlier return to work (mean difference −5.3 weeks; 95% CI: −7.95 to −2.57; p < 0.001) compared with casting. Grip strength was higher (mean difference +2.2 kg; 95% CI: +2.06 to +2.36; p < 0.001), and immobilization duration was shorter (0.5 vs. 8.3 weeks; p < 0.001) with surgery. Secondary surgical intervention was less common in the fixation group (3.2% vs. 7.4%; RR 0.42; 95% CI: 0.21–0.86; p = 0.02), with similar complication rates between groups.Percutaneous screw fixation yields favorable short-term outcomes compared with cast immobilization in adults with non-displaced or minimally displaced scaphoid waist fractures. These findings support its use in appropriately selected patients, while highlighting the need for standardized imaging and follow-up protocols and further study of long-term outcomes.Level I.
Keywords: cast; percutaneous; scaphoid; screw; union